The potential osteogenic effect of stem cells in mandibular distraction in goats - Eman B Elshal; Sayed B Ahmed; Alaa El Deen Jamal Ben Taleb; Yasser N El Hadidi; Marwa El Kassaby; Khaled Abd El Meneim Abd El Kader; Salah Abd El Fatah (Wolters Kluwer Medknow Publications, 2016)
Background Mandibular distraction osteogenesis is a powerful reconstructive tool for the repair of lower-jaw deformities. Mesenchymal stem cells (MSCs) have been initially identified in bone marrow as nonhematopoietic stem cells that may differentiate into different tissues. Objective The objective of this study was to construct an original experimental model for mandibular distraction osteogenesis in the lower jaw, followed by MSC injection that could produce a sufficient quantity and quality of intramembranous bone. Materials and methods Seventeen goats (Capra aegagrus hircus), each weighing about 10-15 kg, were divided into three groups: zero control (n=3), positive control (injured with spontaneous cure) (n=7), and treated (injured and treated by stem cells) groups (n=7). A monodirectional distractor was designed and fixed. Distraction was performed at a rate of 1 mm per day for 10 days to create a distracted gap of 10 mm. In the treated group, after 10 days of distraction, the prepared stem cells (three million cells) were applied in the distracted gap on two doses every 10 days. The treated and positive control group had 30 days of consolidation to allow healing and maturation of the distracted bone. After animal sacrification, histological and radiographic assessments were carried out. Results Cone beam computed tomography examined the radiographic bone density of the newly formed bone, and there was a statistically significant increase in the bone density in the treated group compared with the control group. There was a significant increase in trabecular bone thickness and decrease in osteoid bone percentage in the treated group as compared with the positive control, indicating more rapid bone maturation. Conclusion MSC injection into the distracted mandible induced osteogenesis in the lower jaw of the goats and improvement in bone regeneration.